PERAN GURU DALAM MENUMBUHKAN KARAKTER JIWA WIRAUSAHA PADA PESERTA DIDIK DI UPT SPF SDN PATOMPO 2 KOTA MAKASSAR - Andriani Djabar (Jurnal Ilmiah Pena: Sains dan Ilmu Pendidikan, 2022)
This study aims to find out how the role of teachers in fostering entrepreneurial spirit character in students at UPT SPF SDN Patompo 2 Makassar City This research is a qualitative research with a descriptive approach. The subjects in this study were the principal and teachers of SDN Patompo 2. Data collection techniques for this study use interviews, observations and documentation while the data analysis techniques used include data reduction, data presentation and conclusion drawing / verification The results showed that the role of teachers in fostering the character of the entrepreneurial spirit in students at SDN Patompo 2 Makassar City where teachers have carried out their roles as educators and teachers by integrating learning materials with the character of the entrepreneurial spirit, teachers foster the character of entrepreneurial spirit to students by providing motivation. In addition, teachers become mediators and facilitators in learning in cultivating the character of the entrepreneurial spirit and conducting evaluation activities to find out students' understanding and knowledge about the character of the entrepreneurial spirit. The character of the entrepreneurial spirit that is grown in students is, honesty, discipline, responsibility, cooperation, curiosity, and communication. Obstacles in cultivating the character of the entrepreneurial spirit come from within the students, the support of the family environment is lacking, the community environment and the availability of facilities and infrastructure to carry out entrepreneurial activities in schools that are not adequate. Keywords : Teacher Role, Character, Entrepreneurial spirit